GLOBALISATION AND EXTERNAL CIRCULAR MIGRATION. THE CASE OF ROŞIA MONTANĂ COMMUNITY (ROMANIA) - Pascaru, Mihai; Babut, Teodora Mirela (European Scientific Journal, ESJ, 2015)
The paper looks at the possible relationships between globalisation (glocalisation) and circulatory migration. The starting premise is that for countries with emerging economies like Romania, foreign investment - as vectors of globalisation - may create an exceptional, multidimensional opportunity for work force occupation. In that respect, globalisation should lead to a decrease in all forms of migration. Our research shows however that in particular situations like that of Roşia Montană community, the real impact of foreign investment on workforce occupation turns out to be less than expected. Thus circulatory migration appears as a strong contender for globalisation while everywhere else the globalisation is being regarded as an alternative to endogenous development.